ROLE OF BCG IN PREVENTING CHILDHOOD TUBERCULOSIS - Gillani, Saima; Kazmi, Nasir Hussain Shah; Kamal, Muhammad (Pakistan Journal of Physiology, 2018)
Background: Childhood tuberculosis claims many lives and BCG vaccine is the only prevention available against its most serious forms. Objective was to find out protective role of BCG vaccine against childhood tuberculosis by calculating odds ratio. Methods: It was a case control study. The study was conducted at Paediatrics department of Ayub Teaching Hospital. A total of 308 patients were included in the study. One hundred and fifty-four patients admitted in paediatrics ward and diagnosed with pulmonary, extra pulmonary, disseminated or any other forms of tuberculosis were included as cases in the study. For the control group, 154 children free of tuberculosis were selected as age matched controls from paediatric outpatient department. BCG scar was checked over right upper deltoid in both cases and controls. Data was recorded and analysed using spss. Results: From a total of 308 patients 167 (54.22%) were males and 141 (45.78%) were females. BCG scar was found in 170 (55.19%) out of 308 patients and it was absent in 138 (44.81%) children. Only a slight preponderance among males was noted who were affected by tuberculosis (50.9%) as compared to females from which (48.9%) of total were affected. Odds ratio for presence or absence of BCG scar and presence or absence of tuberculosis was less than 1, i.e., 0.692 (95% CI: 0.441 to 1.086). Administration of BCG vaccine was not a potent protective factor in our study. Pearson’s two tailed correlation between BCG scar and presence or absence of tuberculosis showed p>0.05 and was statistically not significant. Conclusion: There was no significant protective effect of BCG against childhood tuberculosis. Pak J Physiol 2018;14(2):46–9